2003
DOI: 10.1063/1.1564869
|View full text |Cite|
|
Sign up to set email alerts
|

Second-order generation of point defects in gamma-irradiated float-zone silicon, an explanation for “type inversion”

Abstract: Radiation-induced defects in silicon diodes were investigated after exposure to high doses of Co60-gamma irradiation using the thermally stimulated current method. We have found that, for high irradiation doses, a second-order defect can be detected. This defect is largely suppressed in oxygen-enriched material while it is the main cause for the space charge sign inversion effect observed in standard float-zone material.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
42
0

Year Published

2004
2004
2015
2015

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(45 citation statements)
references
References 16 publications
3
42
0
Order By: Relevance
“…2a. The quadratic dose dependence (2 nd order generation) of the I p -center was previously found both for the STFZ and DOFZ diodes up to irradiation doses of 2.80 MGy [48,50,51] and is displayed in vacancies and interstitials are mobile) it was suggested that the best candidate is the long searched for defect complex V 2 O. The V 2 O is the only one defect generated by a second order process that was evidenced by Electron Paramagnetic Resonance [53,54] as direct result of irradiation.…”
Section: Deep Acceptor I Pmentioning
confidence: 93%
See 1 more Smart Citation
“…2a. The quadratic dose dependence (2 nd order generation) of the I p -center was previously found both for the STFZ and DOFZ diodes up to irradiation doses of 2.80 MGy [48,50,51] and is displayed in vacancies and interstitials are mobile) it was suggested that the best candidate is the long searched for defect complex V 2 O. The V 2 O is the only one defect generated by a second order process that was evidenced by Electron Paramagnetic Resonance [53,54] as direct result of irradiation.…”
Section: Deep Acceptor I Pmentioning
confidence: 93%
“…The I p -center is a point defect formed via a second order process that is responsible for the observed type inversion effect in oxygen lean material after γ-irradiation [48,50,51]. It was detected so far in three charge states (-, 0 and +), with two levels in the band-gap, a donor level in the lower part (E V + 0.23 eV) and an acceptor level at the middle of the gap (E C -0.55 eV).…”
Section: Deep Acceptor I Pmentioning
confidence: 99%
“…Measurements with methods like Thermally Stimulated Current technique (TSC), Deep Level Transient Spectroscopy (DLTS), Transient Current Technique (TCT), Capacitance-Voltage (C-V) and Current-Voltage (I-V) have revealed a multitude of defects (11 different energy levels listed in [13]) after irradiations with hadrons or higher energy leptons. The microscopic defects have been observed to influence the macroscopic properties of a silicon sensor by charged defects contributing to the effective doping concentration [14,15,16,17,18,19] and deeper levels also to trapping and generation/recombination of the charge carriers (leakage current) [19,20,21,22]. Such quantity of defect levels set up a vast parameter space that is neither practical nor purposeful to model and tune.…”
Section: Radiation Induced Defectsmentioning
confidence: 99%
“…I and Γ are generated in higher concentrations in standard FZ silicon than in oxygen enriched silicon, while the BD is found in oxygen enriched and epitaxial silicon (see Fig. 1) ( [2][3][4]). The Γ defect has an acceptor level at E v + 0.68 eV, linear dose dependence and can explain about 10% of the damage.…”
Section: Defect Characterisationmentioning
confidence: 99%